Factors Influencing Cash Flow Deficiency Among Small And Medium-Sized Enterprises In Melaka - Nor Azah, Abdul Aziz (2008)
The study is conducted to test hypotheses which are to examine whether or not the conjectured relationships have been substantiated and an answer to the research question has been obtained. It is to explain the nature of certain relationships in a situation. This study reports the findings on the factors influencing cash flow deficiency among SMEs in Melaka. The study focused its investigation on six independent variables which are poor bookkeeping, trade credit, slow paying customers, excessive stocks hold, weak credit control management and poor technologies and innovation to the dependent variable of cash flow deficiency. The efforts observed interviewed and distributed questionnaires throughout SMEs in Melaka. It also reviewed overseas and local literatures. Research design was drawn for requisite data to be gathered and analyzed to arrive at a solution. The research design, which involves a series of rational decision-making choices, is presented. Issues relating to decisions regarding the purpose of the study, the type it should conform to (type of investigation), the extent to which it is manipulated and controlled by the researcher (extent of research interference), its location (the study setting), measurement and measures, the level at which the data will be analyzed (unit of analysis), sampling design, its temporal aspects (time horizon), and data collection method are integral to research design. There were 52 samples out of 438 populations of registered SMEs in Melaka which indicates 12% of population; however most of them were micro SMEs and would be the basic focus of this study. The significant of the study is to realize policymakers, strategic planners, managers of SMEs and customers on the state of the importance of what actually matters that can help SMEs to survive and sustain in the market. Results from the analysis shown the significant of independent variables and proved the relationships have been substantiated to the dependent variable which contribute a great influence to ,cash flow deficiency among SMEs in Melaka. It was concluded from the study that ' poor' or 'careless ' financial management (management of the said independent variables) had been identified as a major cause of small business failure. It can cause wrenching problems. Recommendations are business must plan for certain payments, such as payroll expenses, loan payments, payments to key suppliers, payment for assets and so on. Business need to incorporate these payments into cash flow forecasts and then make sure those sufficient funds will be available at those key times. They need to make sure that any purchases are scheduled when cash position is stronger or are structured over a longer time frame to reduce the impact on cash flow.